Poetry In Action Training Based on Local Wisdom at the Budi Mulia Children's Orphanage (PSAA) Banjarbaru - Dewi Fitriani; Ersis Warmansyah Abbas; Muhammad Adhitya Hidayat Putra (Universitas Lambung Mangkurat, 2023)
Literature was born to express the contents of the human heart as well as thoughts as outlined in the form of writing and poetry; the existence of a community in the field of literature to express the heart's expression, explore creativity, increase self-confidence is also being able to elevate local wisdom to the community. This article aims to describe the urgency of local wisdom in South Kalimantan through training in poetry reading and poetry musicalisation Budi Mulia Banjarbaru Children's Orphanage (PSAA), run by a community engaged in the field of literature, especially poetry, is the Akademi Bangku Panjang Minggu Raya, one of the regular activities of Poetry In Action. The training will be held every Friday on 5, 12 and 19 May, 2023. The material's presentation uses various lecture methods and hands-on practice for poetry readings. The results of the dedication can be explained that there are still many orphanages that have not been able to explain appropriately related to literary works based on local wisdom, especially in the area of South Kalimantan, because at school, it is only general knowledge which is only for knowledge but cannot be interpreted as a proud appreciation of local wisdom. This service motivates the younger generation to appreciate and preserve local wisdom.